On the Move to Meaningful Internet Systems: OTM 2016 Conferences Confederated International Conferences: CoopIS, C&TC, and ODBASE 2016, Rhodes, Greece, October 24-28, 2016, Proceedings - Debruyne, Christophe; Panetto, Hervé; Meersman, Robert; Dillon, Tharam; Kühn, eva; O'Sullivan, Declan; Ardagna, Claudio Agostino (Programming and Software Engineering, 2016)
This volume constitutes the refereed proceedings of the Confederated International Conferences: Cooperative Information Systems, CoopIS 2016, Ontologies, Databases, and Applications of Semantics, ODBASE 2016, and Cloud and Trusted Computing, C&TC, held as part of OTM 2016 in October 2016 in Rhodes, Greece. The 45 full papers presented together with 16 short papers were carefully reviewed and selected from 133 submissions. The OTM program every year covers data and Web semantics, distributed objects, Web services, databases, information systems, enterprise work ow and collaboration, ubiquity, interoperability, mobility, grid and high-performance computing.